Re-Visiting Fisher Effect for Fragile Five Economies - Bayat, Tayfur; Kayhan, Selim; Tasar, Izzet (De Gruyter Poland Sp Zoo, 2018)
In this study, we aim to investigate the relationship between interest rate and inflation rate in the context of the Fisher effect hypothesis for Fragile five economies. In this regard, we employ recently developed panel co-integration and panel causality test methods. The bi-directional causal relation between interest rate and inflation rate exists only in Brazil and Indonesia. On the other hand, there is no causation linkage in India. Results imply that Fisher effect exists only in Brazil and Indonesia.
Keywords: Fisher effect; panel data; fragile five economies